Implementasi Pemenuhan Hak Asimilasi bagi Warga Binaan di Lembaga Pemasyarakatan Kelas 1 Surabaya - Wahid, Nirfan Abdul; Rizky, Muchammad Catur; Herningtyas, Tuti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The implementation of assimilation for prisoners is part of the fulfillment of the rights of inmates guaranteed in laws and regulations, especially Law Number 22 of 2022 concerning Corrections and Regulation of the Minister of Law and Human Rights Number 7 of 2022. However, in practice, the implementation of the assimilation program at the Surabaya Class I Correctional Institution has not been running optimally. This study aims to analyze the implementation of the fulfillment of prisoners' assimilation rights and identify the inhibiting factors. This study uses a qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study show that all prisoners normatively have the same rights to obtain assimilation, but its realization has not been achieved due to lack of socialization, unfulfilled administrative and substantive requirements, and the failure to issue post-pandemic technical instructions from the ministry. These findings are analyzed using the theory of legal certainty, legal justice, and legal benefits which show that the fulfillment of rights is not yet balanced with the mandate of the regulation. The conclusion of this study confirms the gap between normative law and implementation in the field. This study contributes by showing the importance of policy reform and strengthening institutional capacity in guaranteeing prisoners' rights equally and effectively.